Futures Panel: Education, Demonstration Needed for People to Accept the New Technology - Eric C. Hope (Journal of Applied Communications, 1979)
I would like to talk with you about a view of the future that will allow us to develop and express ideas more rapidly and easily. A future where technology offers a steady stream of cheaper, faster, smaller and easier-to-use tools that can be used where we work.